Determination of the inhibitory activity of some biological extracts agaiast multi rrsistans antibiotic Staphylococcus specis which and isolated from different sources of infechtion - Raheb salman kurdy; Mohammed Nadhier Maroff (Tikrit Journal of Pure Science)
The study include 225 specimens that were collected from patients attended Tikrit General Hospital from mid of   Septembar to mid December 2016. The specimens included the swab from: burn, wound, otitis media ,pharyngitis, and urine The specimens were incubated on to mannitol salt agar which is considered as selective and differential media for the genus Staphylococcus the results showed that 100 isolate (44,5%)  grown on the medium. According to the phenotypic characteristics and tests biochemical they were Staph. aureus ,Staph. Saprophytis , Staph. sciuri, Staph. Xylosus Staph. lentus Staph. haemolyticusi Staph.c aseolytic